2020
DOI: 10.1002/cbdv.202000217
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial Activity and Molecular Docking Study of Novel α‐(Diphenylphosphoryl)‐ and α‐(Diphenylphosphorothioyl)cycloalkanone Oximes

Abstract: A series of novel α-(diphenylphosphoryl)and α-(diphenylphosphorothioyl)cycloalkanone oximes have been synthesized in search for novel bioactive molecules. Their structures were characterized by various spectroscopic methods including IR, NMR ( 1 H, 31 P, 13 C), mass spectrometry and single crystal X-ray diffraction. The newly synthesized phosphorus-containing oximes were screened for their in vitro antimicrobial activity against Gram-positive bacteria (Staphylococcus aureus and Bacillus subtilis), Gramnegative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
(54 reference statements)
2
8
0
Order By: Relevance
“…S3 in Supplementary Information), revealed that the Z -( 2 ) isomer has the smaller LUMO-HOMO energy gap, indicating a predicted better antibacterial activity than E -( 2 ) isomer. Such results could explain the general tendency observed in our previous study on similar compounds [12] , showing that oximes more rich in Z isomer exhibited a better antibacterial activity.…”
Section: Dft Calculationssupporting
confidence: 79%
See 4 more Smart Citations
“…S3 in Supplementary Information), revealed that the Z -( 2 ) isomer has the smaller LUMO-HOMO energy gap, indicating a predicted better antibacterial activity than E -( 2 ) isomer. Such results could explain the general tendency observed in our previous study on similar compounds [12] , showing that oximes more rich in Z isomer exhibited a better antibacterial activity.…”
Section: Dft Calculationssupporting
confidence: 79%
“…The studied compound C 18 H 20 NOPS ( 2 ) was prepared by using a two-step synthetic pathway from a cyclic enamine, via the oximation of 2-(diphenylphosphorothioyl)cyclohexanone intermediate ( 1 ), according to the recently reported procedure developed by our group [12] .…”
Section: Chemical Preparation Of (2-(hydroxyimino)cyclohexyl)diphenylphosphine Sulfide (2)mentioning
confidence: 99%
See 3 more Smart Citations